Selected plant materials used in migraine therapy - Joanna Piotrowska; Bartłomiej Rospond; Bernadeta Szewczyk; Włodzimierz Opoka (Polish Pharmaceutical Society, 2023)
Migraine is a neurovascular disease characterized by idiopathic, throbbing, usually unilateral headache, accompanied by gastrointestinal disturbances and increased sensitivity to stimuli. Symptoms may persist for several days, and their severity prevents the patient from regular activity. According to estimates, about 3.5 million people of all ages suffer from it in Poland. The disease affects children and adults, with the vast majority (about 80%) of adult patients being women. It does not directly threaten life, but it has a destructive impact on the patient's quality of life, social and family functioning, and professional activity. It should be emphasized that the mechanisms causing migraine are not fully understood. Different types of serotonin (especially 5-HT1) receptors play an essential role in the pathophysiology of migraine. The evidence of the role of the CGRP neuropeptide in the pathomechanism of the development of a migraine attack led to the introduction of monoclonal antibodies (anti-CGRP) into the treatment, whose intravenous or oral administration to patients brings a significant improvement in their clinical condition. In addition, patients receive analgesics, antiemetics, and sedatives. A positive effect on the frequency and severity of migraine pain has a normalized lifestyle, properly selected physical activity, as well as diet. Herbal substances support the prevention of migraine attacks and soothe in the event of their occurrence. Recommended for phytotherapy are ergot, butterbur, feverfew and also ginger, administered as tablets, infusions, or tinctures. Another therapeutic option is the use of drugs and dietary supplements made from dried inflorescences of hemp and cannabis. Preparations containing in their composition tetrahydrocannabinol (THC) with a content greater than 0.2% are available only on prescription with a duplicate. Inhalations with essential oils of peppermint and lavender help alleviate the symptoms of the disease, mainly from the digestive system. It should be remembered that herbal preparations are not without side effects, and their use in migraine therapy should not be continuous. There are few randomized clinical trials confirming the effectiveness of migraine phytotherapy.